2007
DOI: 10.1111/j.1365-3040.2006.01631.x
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis of leaf proteins during dehydration of the resurrection plant Xerophyta viscosa

Abstract: The desiccation-tolerant phenotype of angiosperm resurrection plants is thought to rely on the induction of protective mechanisms that maintain cellular integrity during water loss. Two-dimensional (2D) sodium dodecyl sulphate-polyacrylamide gel electrophoresis (SDS-PAGE) analysis of the Xerophyta viscosa Baker proteome was carried out during dehydration to identify proteins that may play a role in such mechanisms. Quantitative analysis revealed a greater number of changes in protein expression levels at 35% t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
129
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 106 publications
(134 citation statements)
references
References 72 publications
5
129
0
Order By: Relevance
“…Together, these data suggest that, aside from the regulation of electron transport by modulation of the cytochrome b 6 f complex, some components of the system may be degraded. Elevated levels of the thylakoid protease FtsH have been observed at late stages of dehydration of the poikilochlorophyllous resurrection plant Xerophyta viscosa (Ingle et al, 2007), in which degradation of thylakoid proteins is a natural occurrence during desiccation. However, the observation of a similar phenomenon in homoiochlorophyllous types such as Selaginella tamariscina (Wang et al, 2010), H. rhodopensis (Georgieva et al, 2009;Sárvári et al, 2014), and Boea hygrometrica (Jiang et al, 2007) suggests .…”
Section: Decline In Photosynthetic Activity and Protein Levelsmentioning
confidence: 99%
“…Together, these data suggest that, aside from the regulation of electron transport by modulation of the cytochrome b 6 f complex, some components of the system may be degraded. Elevated levels of the thylakoid protease FtsH have been observed at late stages of dehydration of the poikilochlorophyllous resurrection plant Xerophyta viscosa (Ingle et al, 2007), in which degradation of thylakoid proteins is a natural occurrence during desiccation. However, the observation of a similar phenomenon in homoiochlorophyllous types such as Selaginella tamariscina (Wang et al, 2010), H. rhodopensis (Georgieva et al, 2009;Sárvári et al, 2014), and Boea hygrometrica (Jiang et al, 2007) suggests .…”
Section: Decline In Photosynthetic Activity and Protein Levelsmentioning
confidence: 99%
“…This is a highly effective strategy to minimize ROS formation and this may explain why poikilochlorophyllous species appear to remain viable for longer periods than homoiochlorophyllous ones during desiccation [25]. The drawback of this strategy is that reassembly of the photosynthetic apparatus on rehydration requires coordinated transcription and de novo translation [26,28]. Hence, poikilochlorophyllous plants require much longer periods after rehydration to resume normal growth and development.…”
Section: Countering Oxidative and Metabolic Stresses By Modifying Phomentioning
confidence: 99%
“…However, in all three studies, no protein identification was attempted. Recently, changes in the leaf proteomes of resurrection plants during desiccation were examined in X. viscose [28] and in B. hygrometrica [85] using quantitative 2D SDS-PAGE analysis. Several novel gene products, not previously isolated in transcriptomic studies, were identified as being upregulated during [61,86] T. ruralis cDNA libraries enriched with ESTs from slow drying and rehydrating gametophytes revealed genes involved in metabolic recovery, signaling, proteosomal processing, and splicing [94] Lycophyte Selaginella lepidophylla EST library corresponding to approximately 800 genes compared to 1300 genes from desiccation-sensitive S. moellendorfii.…”
Section: Functional Proteomic Studies Of Desiccation Tolerancementioning
confidence: 99%
See 2 more Smart Citations